Nursing care in the management of pain in oncological patients: literature review (Research, Society and Development, 2023)
The control and relief of cancer pain have been a constant concern of the nursing team, during the search for interventions that can reduce or avoid physical-emotional alterations caused by the ineffective management of pain, the nurse acts numerous times with the patient with cancer pain, realizing that the increase in anxiety and discomfort further compromises his general condition. In this context, the responsibility of promoting pain relief and patient comfort requires an accurate assessment of the physiological, emotional, behavioral and environmental aspects that trigger or exacerbate the patient's pain. Thus, the study aimed to understand how nurses interpret pain management in cancer patients. The study consisted of an integrative literature review, based on studies that contain information about methods and protocols that identify how nurses interpret pain management in cancer patients. The searches were carried out in BDENF, through BVS, and SCIELO. As a search strategy, the combination of the following descriptors was used: Nursing care, pain management, cancer pain and therapy. It was concluded that the nursing team requires a very specific education related to pain management in cancer patients, so that the proposed work achieves its objectives, forming a critical thinking about a part of its care model developed in the assessment and management of cancer pain.